Piezoelectric transducer design via multiobjective optimization - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics)
The design of piezoelectric transducers is usually based on single-objective optimization only. In most practical applications of piezoelectric transducers, however, there exist multiple design objectives that often are contradictory to each other by their very nature. It is impossible to find a solution at which each objective function gets its optimal value simultaneously. Our design approach is to first find a set of Pareto-optimal solutions, which can be considered to be best compromises among multiple design objectives. Among these Pareto-optimal solutions, the designer can then select the one solution which he considers to be the best one. In this paper we investigate the optimal design of a Langevin transducer. The design problem is formulated mathematically as a constrained multiobjective optimization problem. The maximum vibration amplitude and the minimum electrical input power are considered as optimization objectives. Design variables involve continuous variables (dimensions of the transducer) and discrete variables (the number of piezoelectric rings and material types). In order to formulate the optimization problem, the behavior of piezoelectric transducers is modeled using the transfer matrix method based on analytical models. Multiobjective evolutionary algorithms are applied in the optimization process and a set of Pareto-optimal designs is calculated. The optimized results are analyzed and the preferred design is determined.
Keywords: Piezoelectric transducer

Multiobjective optimization of piezoelectric transducers using evolutionary algorithms - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Dynamic Behaviour of Elastic Bodies Coupled by Extended Friction Contacts - Genzo, Alexander; Sextro, Walter (Proceedings of ISMA - International conference on noise and vibration engineering)
Keywords: Noise; Vibration engineering

Unsteady rolling contact of rubber wheels - Gutzeit, F; Sextro, Walter; Kröger, Matthias (Analysis and Simulation of Contact Problems)
This paper presents a model for unsteady longitudinal slippage of a loaded rubber wheel. The aim of modelling was to calculate the dynamical contact behavior in a numerical efficient way. Further on, simulation results are compared to experimental data.

Powder coating fabrication by ultrasonic standing wave atomizer - Hemsel, Tobias; Henning, C; Kauczor, Christopher; Littmann, Walter (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Control of Bundled Miniature Ultrasonic Linear Motors - Hemsel, Tobias; Mracek, Maik (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectric linear motor concepts based on coupling of longitudinal vibrations - Hemsel, Tobias; Mracek, Maik; Twiefel, Jens; Vasiljev, Piotr (Ultrasonics)
Classically, rotary motors with gears and spindle mechanisms are used to achieve translatory motion. In means of miniaturization and weight reduction piezoelectric linear motors are of interest. Several ultrasonic linear motors found in literature base on the use of two different vibration modes. Most often flexural and longitudinal modes are combined to achieve an elliptic micro-motion of surface points. This micro-motion is converted to direct linear (or translatory) motion of a driven slider. To gain high amplitudes of the micro-motion and thus having a powerful motor, the ultrasonic vibrator should be driven near the eigenfrequency of its modes. Additionally, low mechanical and electrical losses lead to increased efficiency and large amplitude magnification in resonance. This demands a geometrical design that fits the eigenfrequencies of the two different modes. A frequency-deviation of only a few percent leads to non-acceptable disturbance of the elliptical motion. Thus, the mechanical design of the vibrators has to be done very carefully. Within this contribution we discuss different motor designs based on the coupling of two the same longitudinal vibrations within one structure to generate an elliptic motion of surface points. Different concepts based on piezoelectric plates and Langevin transducers are compared. Benefits and drawbacks against the combination of longitudinal and bending modes will be discussed. Numerical results of the stator vibration as well as motor characteristics are validated by measurements on different prototypes.
Keywords: Piezoelectric linear motor

Model Based Analysis of Piezoelectric Transformers - Hemsel, Tobias; Priya, S (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Model based analysis of piezoelectric transformers - Hemsel, Tobias; Priya, S (Ultrasonics)
Piezoelectric transformers are increasingly getting popular in the electrical devices owing to several advantages such as small size, high efficiency, no electromagnetic noise and non-flammable. In addition to the conventional applications such as ballast for back light inverter in notebook computers, camera flash, and fuel ignition several new applications have emerged such as AC/DC converter, battery charger and automobile lighting. These new applications demand high power density and wide range of voltage gain. Currently, the transformer power density is limited to $40 W/cm{^3}$ obtained at low voltage gain. The purpose of this study was to investigate a transformer design that has the potential of providing higher power density and wider range of voltage gain. The new transformer design utilizes radial mode both at the input and output port and has the unidirectional polarization in the ceramics. This design was found to provide 30 W power with an efficiency of 98% and 30 $\,^{°}$C temperature rise from the room temperature. An electro-mechanical equivalent circuit model was developed to describe the characteristics of the piezoelectric transformer. The model was found to successfully predict the characteristics of the transformer. Excellent matching was found between the computed and experimental results. The results of this study will allow to deterministically design unipoled piezoelectric transformers with specified performance. It is expected that in near future the unipoled transformer will gain significant importance in various electrical components.
Keywords: Piezoelectric transformers

Error-Workspace Analysis of Plane Mechanisms - Hofmeisterro, Adolf; Sextro, Walter; Röschel, Otto (Proceedings of EUCOMES, the first European Conference on Mechanism Science)

Focusing cross-fire applicator for ultrasonic hyperthermia of tumors - Lierke, E.G.; Hemsel, Tobias (Ultrasonics)
An improved concept for ultrasonic hyperthermia of tumors is presented. This concept is based on past experience of a German government supported project [1], which ended in 1984. It offers a low cost alternative to common RF- and microwave methods for hyperthermia of tumors with volumes between 1 and 40 ml at treatment times between 30 and 60 min. Our new version of the system considerably improves the temperature suppression in the healthy tissue around the target area and enables the adjustment of the beam width to the actual tumor size and the field geometry to the depth and shape of the tumor. The applicator can be used for moderate hyperthermia with tissue overheating up to 10 K or for ablation therapy with short high temperature pulses. Its central area is free for the integration of a commercial ultrasonic diagnostic sector scanner or a Doppler flow sensor in order to support the adjustment of the transducer and to monitor the whole area during the therapy.
Keywords: Moderate hyperthermia

Focussing Cross-Fire Applicator for Ultrasonic Hyperthermia of Tumors - Lierke, Ernst-Günter; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Powder Transport by Ultrasonic Waves - Mracek, B; Hemsel, Tobias; Mracek, Maik (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Synergetic driving concepts for bundled miniature ultrasonic linear motors - Mracek, Maik; Hemsel, Tobias (Ultrasonics)
Rotary ultrasonic motors have found broad industrial application in camera lens drives and other systems. Linear ultrasonic motors in contrast have only found limited applications. The main reason for the limited range of application of these very attractive devices seems to be their small force and power range. Attempts to build linear ultrasonic motors for high forces and high power applications have not been truly successful yet. To achieve larger force and higher power, multiple miniaturized motors can be combined. This approach, however, is not as simple as it appears at first glance. The electromechanical behaviour of the individual motors differs slightly due to manufacturing and assembly tolerances. The individual motor characteristics are strongly dependent on the driving parameters (frequency, voltage, temperature, pre-stress, etc.) and the driven load and the collective behaviour of the swarm of motors is not just the linear superposition of the individual drive's forces. Thus, the bundle of motors has to be synchronized and controlled appropriately in order to obtain an optimized drive that is not oversized and costly. We have investigated driving and control strategies of a set of linear ultrasonic motors. Our contribution will be divided into three main parts. In part I ultrasonic linear motors will be introduced. In part II driving strategies for a single motor as well as for a bundle of motors will be presented. These concepts will be verified by simulation results and experimental data. In part III a simplified model for the motor's electromechanical behaviour will be given.
Keywords: Ultrasonic linear motor

Self configuration of a novel miniature ultrasonic linear motor - Mracek, Maik; Vasiljev, Piotr; Hemsel, Tobias; Wallaschek, Jörg (Solid State Phenomena)

Model based design of piezoelectric generators utilizing geometrical and material properties - Richter, Björn; Twiefel, Jens; Hemsel, Tobias; Wallaschek, Jörg (ASME 2006 International Mechanical Engineering Congress and Exposition)
This paper presents a general model based on the electromechanical circuit theory. The model is set up as a mechanical equivalent model for base excited systems and describes the behaviour of a piezoelectric element around one resonance frequency which is sufficient for most practical applications. The model is extended to obtain the influence of geometrical and material properties. The derivated properties are used to describe the parameters of the general model which is easy to handle. Using this model either the calculation of the output power on a specific electric load or the determination of the design of the used piezoelectric element for a needed electric output power is possible. The paper focuses on the design of the ratio of length and width of a piezoelectric bimorph. The validity of the model is shown by the comparison of computed and experimental results.
Keywords: Materials properties; Design; Generators

Comparison of Piezoelectric and Shape Memory Alloy Based Actuators - Schiedeck, Florian; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

The use of shape memory alloy wires in actuators - Schiedeck, Florian; Hemsel, Tobias; Wallaschek, Jörg (Solid State Phenomena)

Contact behaviour of a sliding rubber element - Sextro, Walter; Moldenhauer, Patrick; Wangenheim, M; Lindner, Markus; Kröger, Matthias (Analysis and Simulation of Contact Problems)
Friction occurs in the contact between tyre and road. The friction of rubber material on dry surfaces is dominated by hysteresis and adhesion effects. Hysterisis friction is characterised by the energy dissipation within the visco-elastic material, which is caused by its deformation while passing the surface roughness. Hysteresis effects are modelled by an extended linear visco-elastic material with several Maxwell elements. The development of a model in the time domain allows to consider nonlinear effects. Additionally temperature effects are taken into account based on the WLF-transformation. Adhesion forces originate from molecular bindings between the contact partners. This effect is simulated by applying a modified model of Achenbach on real surfaces. The temperature distribution within the friction contact region is investigated experimentally as well. Furthermore global stick-slip vibrations of a rubber block element are investigated using a global contact model. Numerical results are compared with experiments performed on a tribometer test rig.

Energy harvesting with piezoelectric Elements - Twiefel, Jens; Hemsel, Tobias; Kauczor, Christopher (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)